2015
DOI: 10.1093/mnras/stv528
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic survey of Kepler stars.★ I. HERMES/Mercator observations of A- and F-type stars

Abstract: The Kepler space mission provided near-continuous and high-precision photometry of about 207,000 stars, which can be used for asteroseismology. However, for successful seismic modelling it is equally important to have accurate stellar physical parameters. Therefore, supplementary ground-based data are needed. We report the results of the analysis of high-resolution spectroscopic data of A-and F-type stars from the Kepler field, which were obtained with the HERMES spectrograph on the Mercator telescope. We dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(157 citation statements)
references
References 103 publications
13
143
1
Order By: Relevance
“…Our apparent projected rotation velocity, va sin i = 5.9 ± 0.2 km s −1 is extremely slow compared with the distribution of v sin i for the stars with similar temperatures in the range 7000 T eff 8000 K (Niemczura et al 2015). Their figure 7(e) shows, and their electronic table 3 lists, values of v sin i distributed between 8 and 260 km s −1 , but mostly between 50 and 150 km s −1 (note that they do not take into account macroturbulence, hence their minimum v sin i is overestimated).…”
Section: Rotation Velocity and Magnetic Braking; Ap Starsmentioning
confidence: 58%
See 2 more Smart Citations
“…Our apparent projected rotation velocity, va sin i = 5.9 ± 0.2 km s −1 is extremely slow compared with the distribution of v sin i for the stars with similar temperatures in the range 7000 T eff 8000 K (Niemczura et al 2015). Their figure 7(e) shows, and their electronic table 3 lists, values of v sin i distributed between 8 and 260 km s −1 , but mostly between 50 and 150 km s −1 (note that they do not take into account macroturbulence, hence their minimum v sin i is overestimated).…”
Section: Rotation Velocity and Magnetic Braking; Ap Starsmentioning
confidence: 58%
“…When we plot our ∆T eff = −461 K in their figure 3(a), it is included in the negative scatter range. Niemczura et al (2015) suggested that the accuracy of their spectroscopic temperatures is supported because the temperatures derived from spectral energy distributions agree well with T eff (SPEC) within a scatter of about ±300 K. According to their suggestion, and from an evaluation of the quality of each method, we consider our atmospheric parameters, T eff , log g and [Fe/H] to be more reliable than those from broadband photometry. This is unsurprising.…”
Section: Atmospheric Parametersmentioning
confidence: 73%
See 1 more Smart Citation
“…This approach has been successfully used in a number of papers in the recent literature (see e.g. Niemczura et al 2015;Catanzaro & Ripepi 2014;Hubrig et al 2014;Doyle et al 2014;Paunzen et al 2014;Catanzaro et al 2015, just to quote some recent work). The website by Fiorella Castelli 2 contains a description of all the improvements of the Kurucz codes and related updates in the input physics performed in the latest years.…”
Section: Caos Spectramentioning
confidence: 99%
“…A&A proofs: manuscript no. k0415_v1.1 Niemczura et al (2015); (3) Simbad (Wenger et al 2000); (4) Kepler Input Catalog; (5) 2MASS (Skrutskie et al 2006) the Kepler Eclipsing Binaries Catalog (KEBC; Prša et al 2011;Slawson et al 2011;Kirk et al 2016) 2 . It is usually classified as having a late-A spectral type.…”
Section: Introductionmentioning
confidence: 99%